A model based on equations of kinetics to study nitrogen dioxide behavior within a plasma discharge reactor. Issue 1 (December 2015) - Abedi-Varaki, Mehdi; Ganjovi, Alireza; Shojaei, Fahimeh; Hassani, Zahra
Abstract In this work, a zero-dimensional kinetics model is used to study the temporal behavior of different species such as charged particles, radicals and excited states inside a Dielectric Barrier Discharge plasma reactor. It is shown that, the reactor significantly reduces the concentration of nitrogen monoxide as an environmental pollutant. After a drastic increase, a decrease in the concentration of the NO2 molecules inside the reactor is seen. Nitrogen monoxide molecules with a very low concentration are produced inside the reactor and its quick conversion to other products is proved. The obtained results are compared with the existing experimental and simulation findings, whenever possible.